Selective sensitive finite element model updating: an improved approach. Issue 8 (10th January 2014) - Billmaier, Maximilian; Bucher, Christian; Adam, Christoph
SUMMARY This paper discusses the realization of dynamic excitations that are used to complete finite element model updating, based on the selective sensitivity approach. It is explained how structures with many DOFs respond in desired parameter (in‐) sensitive output patterns and how such patterns can be achieved without substantial previous theoretical knowledge. The excitation of selective sensitive response patterns has been defined in the literature as the fundamental requirement to perform parameter (in‐) sensitive model updating. Up to now, the practical generation of selective sensitive response patterns on existing and possible complex structures has been questionable. Consequently, in this paper, a major effort is dedicated to overcome this problem and to provide an excitation approach that can be realized in practice. In a test example, the system parameters of a continuous steel beam are identified, taking into account the minimum excitation configuration given by four available electro dynamic shakers. The realization of different and independent experimental configurations is shown. Copyright © 2014 John Wiley & Sons, Ltd.